Cercando un yo en fuga: De lejanías de Rosalba Campra (Altre Modernità, 2019)
The search for identity, characteristic of a considerable part of Hispanic American literature, is evident once again, in the poems collected under the title De lejanías by Rosalba Campra in which the author plays with the different formats of the “escrituras del yo” (Different ways to write about myself). However, in spite of this persistent investigation by the author, it is difficult for the reader to grasp her profile because it is continuously escaping, duplicating or it is uncertain or masked. Thus, the text becomes an oxymoron since it reaffirms with persistence an identity through a sentimental or nostalgic confession, but in tracking what is permanent it eludes the same intention of the search.
Keywords: identity; autofiction; conversational poetry; intertextuality